Is Financial Management Mediating the Role of Love of Money and Human Resources Competence in Explaining MSMEs’ Performance? - Netty Herawaty (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2023)
This study aims to analyze the role of financial management in mediating the impact of the love of money and human resource competence on MSMEs’ performance. It used primary data gathered from 143 respondents through a direct survey. The respondents were the owners of culinary MSMEs in the City of Jambi that were selected based on a cluster sampling method to represent all types of culinary MSMEs. Six hypotheses were formulated to achieve the aim of the study. Path analysis based on multiple regression and Sobel tests were applied to test the hypotheses. The analysis results show that human resource competence affects financial management and impacts MSMEs’ performance directly and indirectly. On the other hand, love of money did not impact financial management. It did not impact MSMEs’ performance either directly or indirectly. Thus, this study provides a piece of evidence for financial management as a mediating variable between human resources competence and MSMEs’ performance.